The Tobamoviral Movement Protein: A “Conditioner” to Create a Favorable Environment for Intercellular Spread of Infection - Sheshukova, Ekaterina V.; Ershova, Natalia M.; Kamarova, Kamila A.; Dorokhov, Yuri L.; Komarova, Tatiana V. (Frontiers in Plant Science, 2020)
During their evolution, viruses acquired genes encoding movement protein(s) (MPs) that mediate the intracellular transport of viral genetic material to plasmodesmata (Pd) and initiate the mechanisms leading to the increase in the plasmodesmal permeability. Although the current view on the role of the viral MPs was primarily formed through studies on tobacco mosaic virus (TMV), the function of its MP has not been fully elucidated. Given the intercellular movement of MPs independent of genomic viral RNA (vRNA), this characteristic may induce favourable conditions ahead of the infection front for the accelerated movement of the vRNA (i.e. the MP plays a role as a “conditioner” of viral intercellular spread). This idea is supported by (a) the synthesis of MP from genomic vRNA early in infection, (b) the Pd opening and the MP transfer to neighbouring cells without formation of the viral replication complex (VRC), and (c) the MP-mediated movement of VRCs beyond the primary infected cell. Here, we will consider findings that favour the TMV MP as a “conditioner” of enhanced intercellular virus movement. In addition, we will discuss the mechanism by which TMV MP opens Pd for extraordinary transport of macromolecules. Although there is no evidence showing direct effects of TMV MP on Pd leading to their dilatation, recent findings indicate that MPs exert their influence indirectly by modulating Pd external and structural macromolecules such as callose and Pd-associated proteins. In explaining this phenomenon, we will propose a mechanism for TMV MP functioning as a conditioner for virus movement.